Board Of Directors Accountability In Good Business Practice - Erwin Syahruddin (Ipso Jure, 2025)
In a Limited culpability Company (PT), where directors are frequently held responsible for their acts pertaining to the company's administration, this study examines the legal concerns surrounding the board of directors' culpability. This obligation may result in civil liability, criminal liability, or even removal from office. Finding the legal void surrounding acquit et de charge (free from liability) under Law No. 40/2007 on Limited Liability Companies (UUPT), which does not specifically govern the procedure, is the primary goal of this study. This study employs the normative technique, which focuses on examining relevant laws and regulations, specifically the UUPT, as well as jurisprudence and doctrine pertaining to the Board of Directors' liability. Using this method, the study discovered that while the Company Law governs the Board of Directors' power and duty, there are no explicit guidelines governing the acquit et de charge process in PT's Board of Directors' accountability process. This creates ambiguity in the way the Board of Directors' responsibility to the General Meeting of Shareholders (GMS) is implemented and raises the possibility of power abuse that could hurt family members. In order to give the Board of Directors legal certainty and fairness in the performance of their obligations, this conclusion necessitates additional regulation of the absolve et de charge mechanism.